Plastidial Disproportionating Enzyme Participates in Starch Synthesis in Rice Endosperm by Transferring Maltooligosyl Groups from Amylose and Amylopectin to Amylopectin. Issue 4 (15th October 2015) - Dong, Xiangbai; Zhang, Du; Liu, Jie; Liu, Qiao Quan; Liu, Hualiang; Tian, Lihong; Jiang, Ling; Qu, Le Qing
Abstract : Overexpression or suppression of plastidial disproportionating enzyme affected amylose content, amylopectin structure, and morphological and physicochemical properties of starch granules in rice endosperm. Abstract: Plastidial disproportionating enzyme1 (DPE1), an α-1, 4-d -glucanotransferase, has been thought to be involved in storage starch synthesis in cereal crops. However, the precise function of DPE1 remains to be established. We present here the functional identification of DPE1 in storage starch synthesis in rice ( Oryza sativa ) by endosperm-specific gene overexpression and suppression. DPE1 overexpression decreased amylose content and resulted in small and tightly packed starch granules, whereas DPE1 suppression increased amylose content and formed heterogeneous-sized, spherical, and loosely packed starch granules. Chains with degree of polymerization (DP ) of 6 to 10 and 23 to 38 were increased, while chains with DP of 11 to 22 were decreased in amylopectin from DPE1 -overexpressing seeds. By contrast, chains with DP of 6 to 8 and 16 to 36 were decreased, while chains with DP of 9 to 15 were increased in amylopectin from DPE1 -suppressed seeds. Changes in DPE1 gene expression also resulted in modifications in the thermal and pasting features of endosperm starch granules. In vitro analyses revealed that recombinant DPE1 can break down amylose into maltooligosaccharides in the presence of Glc, while it can transfer maltooligosyl groups from maltooligosaccharide to amylopectin or transfer maltooligosyl groups within and among amylopectin molecules in the absence of Glc. Moreover, a metabolic flow of maltooligosyl groups from amylose to amylopectin was clearly identifiable when comparing DPE1 -overexpressing lines with DPE1 -suppressed lines. These findings demonstrate that DPE1 participates substantially in starch synthesis in rice endosperm by transferring maltooligosyl groups from amylose and amylopectin to amylopectin.